Peningkatan Tertib Administrasi Pendaftaran Tanah dan Literasi Hukum Pertanahan Sebagai Upaya Preventif Pencegahan Kebakaran Hutan dan Lahan di Wilayah Rawan Kabupaten Indragiri Hilir - Bambang Sasmita Adi Putra; Ridwan, Muannif; Azhar , Ali; Gushairi; Syariffuddin; Syaputra, Didi (Indra Institute Research & Publication, 2025)
Forest and land fires (Karhutla) are recurring ecological disasters in vulnerable regions such as Indragiri Hilir Regency. One of the main triggers is the lack of public awareness regarding land ownership legality and weak legal literacy in land administration. This study aims to enhance community legal awareness through legal education activities on the importance of land registration administration and law-based land management as a preventive measure against Karhutla. The method employed is a qualitative participatory approach through field observation, discussion, and evaluation during a community service program in Teluk Dalam Village, Kuala Indragiri District. Participants included village officials, community leaders, and land users. The findings show increased understanding among participants regarding land registration procedures, legal sanctions for land burning, and the importance of legality in securing land rights. The interactive discussions also revealed a shift in public attitude towards traditional land clearing by burning. This study concludes that community-based legal education is an effective approach to developing sustainable legal awareness in fire-prone areas.